How close is too close? Mapping the impact area of renewable energy infrastructure on tourism - Tverijonaite, Edita; Sæþórsdóttir, Anna Dóra; Ólafsdóttir, Rannveig; Hall, C. Michael (Energy Research & Social Science, 2022)
Estimating the spatial extent of the impacts of renewable energy infrastructure on tourism is crucial for the identification of potential locations of resource use conflict. Such a task, however, is complicated and requires inclusion of social perceptions on the spatial extent of the impacts. This study investigates perceptions of the tourism industry in Iceland regarding the impact area of existing and proposed energy projects on tourism and analyses the factors affecting its size and shape. It is based on semi-structured interviews with tourism service providers, during which participants mapped their perceived impact areas using participatory mapping software. The results revealed that the reasoning affecting the perceived spatial extent of the impacts falls into three categories: visibility of renewable energy infrastructure and related environmental impacts; tourist mobility; and changes in tourism due to energy projects. Moreover, the impacts of the proposed energy projects were perceived as more negative compared to existing ones. Energy projects were considered less suitable in wilderness areas, which were defined by the tourism service providers as an important resource for nature-based tourism, but more acceptable in developed areas. Thus, the spatial extent of the impacts and the compatibility of renewable energy infrastructure with tourism highly depend on changes in place meanings and tourism processes brought by energy infrastructure as well as affected elements of tourism networks. This emphasizes the importance of including tourism stakeholder perceptions and knowledge into the early stages of energy planning to ensure sustainable development of both the tourism and energy industries.